Efficient Preparation of Enantiopure D-Phenylalanine through Asymmetric Resolution Using Immobilized Phenylalanine Ammonia-Lyase from Rhodotorula glutinis JN-1 in a Recirculating Packed-Bed Reactor - Zhu, Longbao; Zhou, Li; Huang, Nan; Cui, Wenjing; Liu, Zhongmei; Xiao, Ke; Zhou, Zhemin (PLOS ONE, 2014)
An efficient enzymatic process was developed to produce optically pure D-phenylalanine through asymmetric resolution of the racemic DL-phenylalanine using immobilized phenylalanine ammonia-lyase (RgPAL) from Rhodotorula glutinis JN-1. RgPAL was immobilized on a modified mesoporous silica support (MCM-41-NH-GA). The resulting MCM-41-NH-GA-RgPAL showed high activity and stability. The resolution efficiency using MCM-41-NH-GA-RgPAL in a recirculating packed-bed reactor (RPBR) was higher than that in a stirred-tank reactor. Under optimal operational conditions, the volumetric conversion rate of L-phenylalanine and the productivity of D-phenylalanine reached 96.7 mM h−1 and 0.32 g L−1 h−1, respectively. The optical purity (eeD) of D-phenylalanine exceeded 99%. The RPBR ran continuously for 16 batches, the conversion ratio did not decrease. The reactor was scaled up 25-fold, and the productivity of D-phenylalanine (eeD>99%) in the scaled-up reactor reached 7.2 g L−1 h−1. These results suggest that the resolution process is an alternative method to produce highly pure D-phenylalanine.